(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
The white cane is a tool for independence and a symbol of our sight-impaired citizens. The invention of the white cane was claimed by James Biggs after lost his sight and felt threatened by the traffic near his home. He painted his walking stick white to be more visible to motor riders. The implementation is done in small iterations. Thus, all data are checked regularly and changed if necessary. This approach improved our project and then continued in the design and development phase. It is a methodology that helps the developers to validate the ideas and align the team vision of a product while setting clear goals and objectives. It took a one-week sprint to work through the project construction, testing, and evaluation with the target users. According to the technicality of our project, our device is efficient and reliable to sense the distance of objects and water and determined exact location. Blind people struggle with traveling dependent on the assistance of their custodian or a simple stick to walk to the places they want to go as well as avoiding the obstacles in their path. Their safety is important to avoid accidents and getting lost. Thus, the developed device improved the mobility of blind persons, thereby allowing them to travel independently and helped their custodians to easily monitor them. The implementation of the microcontroller-based blind stick and love with location tracker is a low-cost, simple, portable, and user-friendly. Our device has obstacle detection 20 cm ahead of the user, water detection, location tracker, and sending/receiving SMS to view the real-time data of location. The microcontroller controlled the overall operation of the device and generated a buzzer sound for the obstacle and water detection. The additional feature of our device is a finder for the stick that alarm through a whistle. The system was designed using Arduino IDE (C language).